The Effect of Due Professional Care, Norms, Ethics, and Attitude on Audit Quality - Israa, Ali Ahmed; Al-Tamimib, Abbas Hamid Yahya (Engineering, Technology & Applied Science Research, 2025)
The current study extends the Theory of Planned Behavior (TPB) to examine the factors influencing high-quality financial reports in Iraqi organizations. The employed variables include Subjective Norms (SN), Audit Quality (AQ), Attitude (ATT), Auditor Ethics (AE), and Due Professional Care (DPC). Data were collected from 109 professionals using an online-based survey and were analyzed deploying the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The quantitative findings exhibit that AE, DPC, and ATT can predict high-quality audit reports. In contrast, no statistically significant correlation was observed between SN and AQ. It was concluded that auditors must perform their tasks with expertise, competence, and attention to detail to achieve outstanding AQ. Furthermore, firms and regulatory bodies must prioritize the strengthening of these aspects to improve audit performance and stakeholders’ trust.